DYRK1A in blood and immune function: implications in leukemia, inflammatory disorders, infection and Down syndrome - Rozen, Esteban J.; Dowell, Robin D.; Allen, Mary A. (Frontiers in Cell and Developmental Biology, 2025)
Down syndrome (DS) is the most frequent autosomal aneuploidy, and it arises due to an extra copy of human chromosome 21. Individuals with trisomy 21 (T21) exhibit an increased predisposition towards a wide number of developmental and physiological alterations, often referred to as DS co-occurring conditions, including congenital heart disease, leukemia, intellectual disability, neurodegenerative disorders or autoimmune diseases, among many others. The overexpression of several genes encoded on chromosome 21 have been linked to many of such T21-associated disorders, but we are still very far from grasping a full picture of the contributions and interconnections of such genes in the pathophysiology of DS. DYRK1A is a versatile and ubiquitous kinase encoded on human chromosome 21, and as such, its activity has been linked to many alterations that characterize DS. Although most of the attention has been focused on DYRK1A’s roles in neural development, function and degeneration, accumulating reports are expanding the scope towards other tissues and conditions where this kinase also performs critical functions, such as the cardiovascular system, diabetes, inflammation and immune homeostasis. Here, we present a detailed review of the literature summarizing all the information linking DYRK1A to blood and immune function, as well as leukemia, inflammation and viral infections, with a special focus on their potential associations to T21. This article synthesizes evidence that supports several novel hypotheses on previously unsuspected roles for DYRK1A in specific DS alterations, opening new pathways for the research community to explore and therefore, contributing to future innovative diagnostic or therapeutic interventions. This article will hopefully inspire and guide the advancement of our knowledge leading to much needed treatments for individuals with Down syndrome, but also for the general population.